2014
DOI: 10.1080/23248378.2013.878294
|View full text |Cite
|
Sign up to set email alerts
|

Bogies towards higher speed on existing tracks

Abstract: Running faster on existing tracks is a common operator's wish that should be set in relation to the necessary infrastructure maintenance costs for track quality enhancement. Designing a track-friendly running gear that exerts moderate forces on the track is a key to relax this relation. A design providing good ride quality even on non-perfect track is preferred to avoid excessive track maintenance costs when speeds are higher. This paper describes how simulations and tests have been performed to optimise certa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 2 publications
1
4
0
Order By: Relevance
“…The result is a smoother ride in the car body. According to simulations, at least the same ride comfort can be achieved at 250 km/h with active suspension as at 200 km/h with passive suspension [10]. These results are confirmed by on-track tests at speeds A further advantage of active suspensions is that the suspension movements are reduced, thus allowing a wider car body, further improving passenger comfort.…”
Section: Good Ride Qualities On Non-perfect Tracksupporting
confidence: 81%
See 2 more Smart Citations
“…The result is a smoother ride in the car body. According to simulations, at least the same ride comfort can be achieved at 250 km/h with active suspension as at 200 km/h with passive suspension [10]. These results are confirmed by on-track tests at speeds A further advantage of active suspensions is that the suspension movements are reduced, thus allowing a wider car body, further improving passenger comfort.…”
Section: Good Ride Qualities On Non-perfect Tracksupporting
confidence: 81%
“…Radial self-steering (RSS) bogies, capable of running stably at speeds well above 250 km/h, have been developed and tested [10], both in functional and certification tests and in commercial service for 700,000 km. These bogies have been tested under track conditions exhibiting limit values for 160-200 km/h.…”
Section: Moderate Track Deteriorationmentioning
confidence: 99%
See 1 more Smart Citation
“…To keep higher safety and reliability of bogie frames for a light rail vehicle, three fatigue assessment procedures in terms of equivalent stress ranges have been carefully examined using highly loaded welded joints, such as the endurance limit approach with the maximum loading amplitude, cumulative damage approach with the loading spectrum of fatigue test program, and cumulative damage approach with the vertical force range spectrum from MBS simulation. It has been confirmed that the MBS-based loading spectrum provides more realistic loads, which act on the bogie frame, for fatigue assessment, depending on the actual railway conditions [3,[14][15][16]. However, it is well-known that the fatigue assessment based on the endurance limit approach provides relatively conservative results for the allowable stress and accumulation damage; nevertheless, such an approach serves as a quick and standard procedure for the safe life analysis of railway safety-critical components [17][18][19].…”
Section: Introductionmentioning
confidence: 78%
“…Therefore, a reasonable selection for yaw damper parameters is particularly noteworthy, which can improve lateral ride comfort and reduce the wheel-rail lateral force. [11][12][13][14] Yan et al 15,16 deeply investigated the impact of the yaw damper's damping and series stiffness on the bogie stability and bifurcation type, and integrated the central popular theorem with the paradigm method to acquire the expressions for critical speed and bifurcation types, which were related to the damping and series stiffness of yaw dampers. Xia et al 17 developed a bogie mechanical model with four degrees of freedom, and researched the impression of yaw damper's suspension parameters and installation position on lateral stability, ride comfort and steering ability.…”
Section: Introductionmentioning
confidence: 99%